Chilblain lupus erythematosus – a case report - Zając, Natalia; Markiewicz, Agnieszka; Chuchla-Szczupacka, Katarzyna; Owczarczyk-Saczonek, Agnieszka; Placek, Waldemar (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction . Chilblain lupus erythematosus is a chronic form of lupus erythematosus (LE) reported mostly in middle-aged female patients. Its characteristic manifestations are painful erythematous lesions on the acral parts of the body appearing after exposure to cold. Chilblain lupus erythematosus may either precede the development of systemic lupus erythematosus (SLE) or occur after the diagnosis of SLE is established. It can also be an isolated form of lupus erythematosus. There are no well-defined and reported treating approaches in this form of LE. Objective. Presentation of a case of chilblain lupus erythematosus with reference to current therapeutic options. Case report . We report a 44 year-old patient diagnosed with chilblain lupus (according to Mayo Clinic Proposal of Diagnostic Criteria) who over the years fulfilled the American College of Rheumatology (ACR) classification criteria and was diagnosed with SLE. The patient was treated with different medications with no response. Finally a complex therapy with mycophenolate mofetil, methylprednisolone and pentoxifylline during the exacerbation managed to control the symptoms and brought partial improvement. Conclusions . Chilblain lupus may constitute a therapeutic challenge. The reported case suggests that in therapy-resistant cases, a complex treatment with mycophenolate mofetil, methylprednisolone and pentoxifylline during the exacerbation of symptoms might be considered.